One-Stage Posterior Debridement and Transpedicular Screw Fixation for Treating Monosegmental Thoracic and Lumbar Spinal Tuberculosis in Adults - Zhili Liu; Jiaming Liu; Aifeng Peng; Xinhua Long; Dong Yang; Shanhu Huang (The Scientific World Journal)
Spinal tuberculosis is still prevalent in some developing countries. The purpose of this study is to investigate the efficacy and safety of one-stage posterior debridement, autogenous bone grafting, and transpedicular screw fixation in treating monosegmental thoracic and lumbar tuberculosis in adults. 37 patients were retrospectively reviewed in this study. The data of images, operative time and blood loss volume, perioperative complications, time to achieve bony fusion, VAS score, and neurologic function preoperatively and postoperatively were collected. The mean follow-up period was 21.5±3.5 months. The tuberculosis was cured after surgery in all patients, and no recurrence was observed. Bony fusion was achieved in all patients with a mean time of 5.6±2.5 months. Neurological outcome did not change in one case with grade A, and increased by 1–3 grades in the other patients with nerve deficit. The average preoperative and postoperative VAS scores were 5.5±2.23 and 1.5±1.22, respectively; the difference was significant (P<0.05). There were three perioperative complications (8.1%, 3/37) observed in this study. In conclusion, the procedure of one-stage posterior debridement, interbody fusion with autogenous bone grafting, and posterior fixation with pedicle screw is effective and safe for treating monosegmental thoracic and lumbar spinal tuberculosis in adults.